2009
DOI: 10.1073/pnas.0907857106
|View full text |Cite
|
Sign up to set email alerts
|

An independent evaluation of the Younger Dryas extraterrestrial impact hypothesis

Abstract: Based on elevated concentrations of a set of “impact markers” at the onset of the Younger Dryas stadial from sedimentary contexts across North America, Firestone, Kennett, West, and others have argued that 12.9 ka the Earth experienced an impact by an extraterrestrial body, an event that had devastating ecological consequences for humans, plants, and animals in the New World [Firestone RB, et al. (2007) Proc. Natl. Acad. Sci. USA 104:16016–16021]. Herein, we report the results of an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
78
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 14 publications
4
78
0
Order By: Relevance
“…Still others raised concerns over issues of replicability and laboratory protocols used in the original study (15). Here, we provide evidence that supports an alternative hypothesis for the accumulation of some of the markers in late Quaternary sediments.…”
supporting
confidence: 71%
“…Still others raised concerns over issues of replicability and laboratory protocols used in the original study (15). Here, we provide evidence that supports an alternative hypothesis for the accumulation of some of the markers in late Quaternary sediments.…”
supporting
confidence: 71%
“…Also, in a Greenland ice core, Petaev et al (2013) found a large YDB abundance peak in the platinumgroup element platinum. Surovell et al (2009) found no YDB peaks in magnetic spherules, whereas LeCompte et al (2012) found large, welldefined YDB spherule peaks at sites common to the study by Surovell et al Also, critical overviews of the YDB hypothesis are presented in Pinter et al (2011) and Boslough et al (2012).…”
Section: Introductionmentioning
confidence: 86%
“…Consequently, determining the nature and origin of observed spherules is essential. Attempts to replicate the spherule abundances and peaks observed by (17) confirmed the presence of YDB spherules, while studies by Surovell et al (18) and Pinter et al (19) did not. Surovell et al examined sediment sequences across the YDB at seven archeological sites in North America, using radiocarbon dates and/or diagnostic cultural artifacts to identify the stratum likely to be the YDB.…”
mentioning
confidence: 91%
“…A number of independent groups have confirmed the presence of YDB spherules, but two have not. One of them [Surovell TA, et al (2009) Proc Natl Acad Sci USA 104:18155-18158] collected and analyzed samples from seven YDB sites, purportedly using the same protocol as Firestone et al, but did not find a single spherule in YDB sediments at two previously reported sites. To examine this discrepancy, we conducted an independent blind investigation of two sites common to both studies, and a third site investigated only by Surovell Firestone et al) proposed that a cosmic impact event occurred at the onset of the Younger Dryas (YD) cooling episode at about 12,900 calendar years Before Present (12.9 ka B.P.).…”
mentioning
confidence: 99%